Apolipoprotein E genotype is not associated with cognitive impairment in older adults with bipolar disorder. (15th February 2016) - Kerr, Daniel Shikanai; Stella, Florindo; Radanovic, Márcia; Aprahamian, Ivan; Bertollucci, Paulo Henrique Ferreira; Forlenza, Orestes Vicente
Abstract : Objectives: Cognitive decline is part of the long‐term outcome for many individuals with bipolar disorder (BD). The ε4 allele ( APOE*4 ) of apolipoprotein E ( APOE ) is a well‐established risk factor for dementia in Alzheimer's disease (AD). However, its contribution to the risk of cognitive deterioration in BD has not yet been determined. Our aim was to analyze the APOE genotype association with cognitive status in a sample of older adults with BD and compare this to the association in individuals with AD, individuals with mild cognitive impairment (MCI), and healthy controls. Methods: Participants (n = 475) were allocated to four groups: individuals with BD (n = 77), those with AD (n = 211), those with MCI (n = 43), and healthy controls (n = 144) according to clinical and neuropsychological assessment. APOE was genotyped by real‐time polymerase chain reaction. Tukey's honest significant difference test and Pearson's chi‐squared test were used to compare diagnostic groups. Results: Subjects with BD were similar to controls with respect to the distribution of the APOE genotype (p = 0.636) and allele frequencies (p = 0.481). Significant differences were found when comparing the AD group to the BD group or to controls ( APOE genotype: p < 0.0002; allele frequencies: p < 0.001). APOE*4 was significantly increased in the AD group when compared to the BD group (p = 0.031) and controls (p < 0.0001). The cognitively impaired BD subgroup (Mini‐Mental State Examination below the cutoff score and/or neuropsychological assessment compatible with MCI) had a statistically significant higher frequency of APOE*2 compared to the AD group (p = 0.003). Conclusions: APOE*4 is not associated with the diagnosis of BD and does not impact the occurrence of dementia in BD. Given the distinct clinical and biological features of cognitive impairment in BD, we hypothesized that dementia in BD is unrelated to AD pathological mechanisms.